Efl Students’ Problems In Dealing With Teacher Written Feedback - Anggoro Kurnia (Jurnal Pendidikan Indonesia, 2022)
This study aims to determine EFL Students’ problems in dealing with teacher written feedback and their strategies to deal with them. This study used a qualitative method. Data were collected using one instrument, namely interviews with 10 students who have lowest writing scores in 10 grades. The results of the study reported that there were several problems experienced by students, such as difficulty understanding teacher’s comments, difficulty understanding error codes, inability to correct errors based on teacher written feedback and students' fear of asking questions. In addition, students used several strategies to deal with these problems, such as rewriting the teacher feedback with their own words, looking up the meaning of incomprehensible symbol and sentences on the internet/dictionaries and trying to be brave to ask the teacher. This study concludes that the teacher's written feedback must had several aspects namely, effective, easy to understand, easy to follow and precise. This research was expected to find out students' problems and provide solutions to improve their writing skills.